Contribution Margin Analysis as a Tool for Profit Planning in the PT Labiva Jaya Utama Travel Services Business in Parepare - Adri Sallo; Inggriani Elim; Lidia Mawikere (Indonesian Journal of Advanced Research, 2024)
Contribution margin is the result of sales that have been reduced by all variable costs for production and marketing which can cover fixed costs and produce a profit in total per unit. This research aims to find out how to calculate the contribution margin and to be able to find out the contribution margin as a tool for profit planning. The method used in this research is a qualitative research method that uses a descriptive approach and data is also obtained from direct interviews and documentation. The research results show that the contribution margin of PT. Labiva Jaya Utama in 2020 amounted to IDR 79,760,000, in 2021 it amounted to IDR 87,850,000 and in 2022 it amounted to IDR 62,760,000. By calculating the margin, it makes it easier for the company to calculate the level of profit earned by the company each year.